Grasp the Shield Firmly the Journey is Hard : A History of Luo and Bantu migrations to North Mara, (Tanzania) 1850-1950 - Siso, Zedekia Oloo (Book collections on Project MUSE., 2010)
This book is a compilation of oral histories about the movement of Luo and some Bantu-speaking peoples. It includes histories of many clans or ethnic groups, and how drought, warfare, disease, and competition over pastoral resources in western Kenya forced them to look for a land that they could call their own. Highly entertaining, the stories cross over from pre-colonial to post-colonial eras, with tales of fooling the colonial officers, winning battles and producing miracles. Although warriors and chiefs play a critical part in the stories so too do unlikely actors such as women, prophets, a.